LOYALITAS MEREK SEBAGAI DAMPAK DARI KEPUASAN KONSUMEN - Widjaja, Yani Restiani; Nugraha, Irpan (Universitas Islam Negeri Raden Intan Lampung, 2016)
Abstract-This study aims to analyze the influence of customer satisfaction on brand loyalty soap sapokalinus PT BRATACO Bandung. This research is a descriptive study. The study population was a chemist who buy soap sapokalinus PT BRATACO Bandung in the past year. Sampling using Slovin formula, then the sample in this study were 70 respondents. The sampling technique used is the technique of random sampling. The type of data used are primary data and secondary data. Data collection techniques used were questionnaires. Data analysis techniques are simple regression analysis. Hypothesis testing using t test (t-test). The results showed that customer satisfaction significantly influence brand loyalty.